Evaluating the Impact of Gliricidia sepium-Based Alley Cropping Practices on Growth and Yield of Stem Amaranth (American Journal of Agricultural Science, Engineering, and Technology, 2025)
Field experiments were performed to study the feasibility of growing stem amaranth in alley cropping system under different alley widths and nitrogen (N) doses. The experiments were set up following split-plot design with three replications. Three alley widths of Gliricidia sepium viz. 3.0 m, 4.5 m, and 6.0 m (W3.0, W4.5, and W6.0) comprised the main plot treatment, and five nitrogen (N) doses viz. N0, N25, N50, N75, and N100 (0%, 25%, 50%, 75%, and 100% of recommended N doses, including pruned biomass from G. sepium) were distributed as sub-plot treatments. Control plots (without tree) received allied N doses but no pruned material was added. The findings showed that, yield and most of the yield attributes of stem amaranth were found higher in alley cropped plots compared to the control. It was found that, the 3.0, 4.5, and 6.0 m alley widths provided 32, 52 and 68% higher yields of stem amaranth compared to the control (without trees). Gliricidia sepium-established alley cropping augmented the crop yields, where the highest stem amaranth yield (55.57 t ha‒1) was recorded in 6.0 m alley width with 100% N dose which was statistically similar to 75% and 50% N doses in the wider alley width (6.0 m). The above findings suggest that Gliricidia sepium-based alley cropping is a potential approach for increasing crop productivity and reducing synthetic N fertilizer use.